Theoretical investigation of permeable segmented generator thermoelement on the base of Bi-Te, Pb-Te, Si-Ge - Cherkez, R.; Zhukova, A.; Izvak, Y.A.; Cherkez М.; Stefuk, A. (Physics and Chemistry of Solid State, 2022)
Results of computer study on permeable segmented generator thermoelement under efficiency-optimal operating conditions are set forth. Method for solving a multi-parameter optimization problem is described. Heat carrier flow rate, electric current density, parameters of current carrier concentration in each leg segment whereby energy conversion process is maximum thermodynamically efficient are determined. The results of research on a permeable segmented generator thermoelement based on Ві-Те, Pb-Te, PbTeG, Si-Ge materlals are presented. Comparison to conventional thermoelements showed the possibility of efficiency increase by 30 – 40% and generated power by 20-30%.